Information and Communication Technology Competence of Islamic Education Teachers - Bagus Malik Alindra; Evi Fatimatur Rusydiyah; Nita Yalina (Jurnal Pendidikan Islam Indonesia, 2022)
Abstract : Information and Communication Technology has played its role in the educational process. It can be seen from the progress of the globalization era, teachers, especially Islamic Education teachers that must adapt and have ICT competencies that are in accordance with the needs of students in the learning process. Therefore, Islamic Education teachers must be able to develop their ICT competencies in the learning process, so that the learning process can run as expected in this era of globalization. This study used a qualitative method using a questionnaire interview instrument. The informants used were five Islamic Education teachers in the subjects of fiqh, moral aqidah, Qur'an hadith, SKI and Arabic. Then, the object used was the Islamic educational institution at MI Riyadlul Qori'in Ajung Jember. The results of this study were Islamic Education teachers at MI Riyadlul Qori'in that shown good ICT competencies from the four categories of ICT competencies. Key words : Competency, ICT, Islamic Education teacher